The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/1806-9282.20210379
|View full text |Cite
|
Sign up to set email alerts
|

Hesitation regarding the COVID-19 vaccine among medical students in Brazil

Abstract: RESULTS: Most students (84%) mentioned the intention to take anti-COVID vaccine and 14% were hesitant. Information provided by governments (59.2%), the pharmaceutical industry (54.4%), and the press (51.6%) were the items that most generated vaccine hesitation. CONCLUSION:In the context of the COVID-19, vaccine hesitation is an additional concern because adherence to vaccination is a recurring challenge. The category of contextual influences predominated among the main determinants of anti-COVID vaccine hesita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Social media was the most commonly reported resource in our study to obtain information about the vaccine, which is in line with the common preference of current youth to use social media. To keep up, government and health-based agencies have also turned to social media to spread updates about the disease and provide further information; however, in some countries, people are less likely to trust the government which can be observed from a study conducted in Brazil showed that information provided by governments, the pharmaceutical industry, and the press were the items that caused most vaccine hesitancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Social media was the most commonly reported resource in our study to obtain information about the vaccine, which is in line with the common preference of current youth to use social media. To keep up, government and health-based agencies have also turned to social media to spread updates about the disease and provide further information; however, in some countries, people are less likely to trust the government which can be observed from a study conducted in Brazil showed that information provided by governments, the pharmaceutical industry, and the press were the items that caused most vaccine hesitancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of VH among medical students in the studies reviewed ranged from 5.4% to 86.7% (see Table 1 ). Most studies reported VH/VA among medical students, with a small number [ 26 , 27 , 54 , 56 , 67 ] reporting absolute VR rates which ranged from 2% to 17.3%. Saied et al (2021) reported the highest refusal rate with 17.3% of their medical student cohort refusing COVID-19 vaccination [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher rates of VH were observed in African and Middle Eastern countries, with medical students reporting higher rates of belief in conspiracy theories about COVID-19 vaccines [ 34 , 48 , 50 , 63 ]. There was also greater mistrust in government and public health experts’ COVID-19 vaccine information and a higher level of trust placed in the opinions of family members, relatives, and social media when making vaccination decisions within VH populations [ 27 , 36 , 37 , 43 , 64 , 65 ]. It has been demonstrated this mistrust, which has been demonstrated in all HCWs and not just medical students, stems in part from perceived dishonesty of pharmaceutical companies and Government institutions involved in the production, distribution, and/or promotion of vaccines and vaccination protocols [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding political factors, studies conducted in Brazil and Venezuela mentioned opposition to the vaccine of their respective presidents Jair Bolsonaro and Nicolás Maduro 42 , 43 , 47 , 48 , 49 . Maduro questioned the safety of the AstraZeneca vaccine, even refusing to buy it, and because his government was not recognized by many nations 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Maduro questioned the safety of the AstraZeneca vaccine, even refusing to buy it, and because his government was not recognized by many nations 42 , 43 . In Brazil, part of supporters of then President Jair Bolsonaro rejected the COVID-19 vaccine, based on Bolsonaro’s speech in relation to the vaccine as an individual choice and the criticism to the Sinovac-CoronaVac vaccine, produced by a Chinese pharmaceutical company 47 , 48 , 49 . The negative perception of coping with COVID-19 and the political opposition to the Federal Government were associated with the intention to be vaccinated 49 , in addition to the political context of delay in the acquisition and availability of COVID-19 vaccines and political disputes between federal and state governments 47 , 49 .…”
Section: Resultsmentioning
confidence: 99%